A novel methodology for evaluating the inhibitory effect of chloride salts on the ignition risk of coal spontaneous combustion. (15th September 2021) - Lv, Hongpeng; Li, Bei; Deng, Jun; Ye, Lili; Gao, Wei; Shu, Chi-Min; Bi, Mingshu
Abstract: When coal dust accumulations are exposed to air for a period of time, they are gradually oxidised by oxygen. This eventually leads to ignition, causing fires and explosions and exerting a pernicious environmental impact. In the present study, the ignition risk of coal spontaneous combustion (CSC) under the influence of NaCl, KCl, and MgCl2 solution was analysed using hot plate tests. Methods for determining the suppression efficiency of each of the chloride salts were designed according to the minimum ignition temperature of the dust layer and ignition delay time. An evaluation methodology with consideration of both temperature and time parameters was formulated. The results showed that the maximum inhibitory effect and the minimum risk index were observed when MgCl2 solution was used. Moreover, the mechanisms by which the salts suppressed CSC was investigated and compared according to their physicochemical effects. Notably, NaCl and KCl promoted CSC in the smouldering process, whereas the hydrate formed by MgCl2 solution (MgCl2 ·6H2 O) consistently inhibited CSC. The methodology proposed in present study provides significance access to evaluate the ignition risk of CSC in industrial sites where coal dust accumulates. Highlights: NaCl, KCl, and MgCl2 were used as inhibitors to study the ignition risk of CSC. The hot plate test was used to simulate the typical industrial scenarios. By establishing the risk indicator matrix, the ignition risk index was calculated. Of the three chloride salts, MgCl2 had the best inhibitory effects on CSC.